Corporate social responsibility innovation as a counterstrategy of national brand manufacturer against private label. Issue 3 (8th January 2020) - Xu, Heng
Abstract : Purpose: This paper aims to investigate the national brand manufacturer's ability from corporate social responsibility (CSR) innovation as a counterstrategy against the private label by a retailer. By constructing a model of manufacturer–retailer interaction, the paper attempts to analyze that the national brand manufacturer's decision on the CSR innovation and the effect of such innovation on the retailer's motivation of launching the private label. The results of the theoretical model in this paper could be applied by the actors in supply chains in making decision on CSR innovation and the launch of a new brand. Design/methodology/approach: The theoretical model in the paper describes a manufacturer–retailer interaction with the presence of the private label and CSR innovation on the national brand. Specifically, the manufacturer has option of innovating its products and makes them to be more socially responsible; in the meanwhile, the retailer has option of launching its private label. Moreover, there are heterogeneous consumers with respect to their preferences on the CSR feature. The altruistic consumers prefer the socially responsible product while the normal consumers are indifferent between the socially responsible and basic products. By predicting the expected profit, the two firms make decision over the supply chain. Findings: The authors find that the CSR innovation can indeed restrict the retailer's incentive to launch the private label. Because of the presence of the altruistic consumers, the CSR innovation can help the national brand product to expand its market relative to the situation without the innovation. They demonstrate that the national brand manufacturer wishes to invest more in CSR innovation under non-linear pricing contract and the retailer is more likely to launch the private label. This is because that the non-linear pricing contract makes the two firms to concern more about their joint profit, causing the competition is less fierce. Originality/value: This paper explains that the CSR innovation in the national brand product can be an effective counterstrategy by the manufacturer to deter the launch of the private label, which has not been considered by the existing studies about national brand-private label competition. Moreover, this paper also shows that the CSR innovation may benefit both the national brand manufacturer and the retailer under some conditions. In addition, the results of the paper provide some insights to the national brand manufacturer when making decision on the CSR innovation and to the retailer when reacting the manufacturer's CSR innovation.